PERLINDUNGAN KONSUMEN TERHADAP WANSPRESTASI PELAKU USAHA - Onan Purba; Rumelda Silalahi (Jurnal Darma Agung, 2019)
In this study the author examines the consumer protection against the breach contract of business actors. This is based on the reality occurs in the midst of society that there are some business actors harm consumers’ rights. Consumers’ rights are often ignored by business actors as they don’t fulfill their obligations to the consumers properly. This condition can reduce or even lost the trust of the consumer, furthermore the consumer also can take some law process due to this condition. This study uses a normative method, which analyze the problem through an approach in legislation and also sourced from books, papers, laws and other references. There are three problems formulated in this study (1) the legal protection of the consumers to the business actors, (2) the sanctions based on Law Number 8 of 1999 against business actors in transactions, (3)the relationship between business actors and consumers. The existence of a law governing consumer protection is not intended to kill the performance of business actors. The consumer protection law can actually encourage a save business climate and encourage the innovation of a strong company in dealing with existing competition by providing qualified goods / services. This condition also presents two side of negative and positive challenge at a same time. It is positive because it gives a free chance for the consumer to choose any product and services according to their needs. However, it is negative because finally it determined the consumer position which is lower than the business actors. Consumer protection against the breach contract of business actors' should provide transparency contains and open access to information and guarantees legal certainty, protecting the interests of consumers and the interests of all business actors.